Insect ventral radar cross-section polarisation dependence measurements for radar entomology - Hobbs, Stephen; Aldhous, Anthony C. (Institution of Engineering and Technology (IET), 2006)
Radar entomology has developed such that routine long-term monitoring of insect flight through the atmospheric boundary layer is now practical. Typical entomological radars use X-band (9.4 GHz) marine transceivers with a vertical pencil beam and rotate the plane of polarisation about the beam axis. Ideally, insect species and other parameters (mass etc.) should be estimated from the measured radar cross-section variation with polarisation angle. For this, a library of known insect cross-section polarisation signatures is required. Two models are currently used to parameterise the polarisation signature: the harmonic model and a model using the scattering matrix for symmetric targets (SM3). Data from the literature and a doctoral research project are presented and analysed to obtain parameters for both the harmonic and SM3 models. Knowledge of the measurement errors allows SM3 parameter uncertainties to be quantified in most cases using a maximum likelihood approach. Results for 68 insects representing 24 species are presented. These include several economically significant species (e.g. bees and locusts), with individual insect masses ranging from 9 mg to 3 g